2018
DOI: 10.1186/s13071-018-2771-2
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi load in synanthropic rodents from rural areas in Chile

Abstract: BackgroundTrypanosoma cruzi is the agent of Chagas disease, a major public health problem in Latin America. Many wild and domestic animals are naturally infected with T. cruzi; rodents are one of the groups which have been consistently detected infected in different countries. The aim of this work was to characterize blood T. cruzi load in naturally infected rodents from a Chagas disease endemic region in Chile.MethodsBaited traps were set in domestic and peridomestic areas of rural dwellings. The rodents were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Since the home range of triatomines is also small [22], these mammals can act as important T . cruzi hosts, acquiring and maintaining the infection [23, 24]. Infected species in Chile are the rodents Octodon degus , Phyllotis darwini , Abrothrix olivaceus , Rattus rattus , the lagomorph Oryctolagus cuniculus , and the marsupial Thylamys elegans , ranging from 32% to 83.6% [18, 23, 2527].…”
Section: Introductionmentioning
confidence: 99%
“…Since the home range of triatomines is also small [22], these mammals can act as important T . cruzi hosts, acquiring and maintaining the infection [23, 24]. Infected species in Chile are the rodents Octodon degus , Phyllotis darwini , Abrothrix olivaceus , Rattus rattus , the lagomorph Oryctolagus cuniculus , and the marsupial Thylamys elegans , ranging from 32% to 83.6% [18, 23, 2527].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 13 species have been tested for T. cruzi infection, including three Abrothrix species, two Octodon species, Abrocoma bennetti , Chinchilla lanigera , Lagidium viscacia , O. longicaudatus , Phyllotis darwini , and Spalacopus cyanus , among others. From these, seven species have been reported as being infected by T. cruzi , with a high variation in the frequency of infection, mainly depending on the detection technique: A. bennetti (0–42.9%), Abrothrix longipilis (0–9.5%), Abrothrix olivaceus (0–71.0%), C. lanigera (20.0–40.0%), Octodon degus (8.3–70.4%), O. longicaudatus (0–50.0%), and P. darwini (0–100%) [ 14 , 15 , 17 , 29 , 30 , 31 , 32 , 33 , 34 , 40 , 41 , 42 , 43 , 44 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. See the detailed information in Table 2 and Table S1 in Supplementary Materials .…”
Section: Resultsmentioning
confidence: 99%
“…In the 1940s, the prevalence of T. cruzi infection in R. rattus , R. norvegicus and M. musculus was tested by optical microscopy and/or XD but no infection was detected [ 29 ]. Recent studies, using molecular detection (cPCR, hemi-nested PCR, and/or qPCR), have reported a high infection prevalence: R. rattus (27.7%, 83.6%), R. norvegicus (71.4%), and M. musculus (83.3%) [ 14 , 34 , 48 , 56 ]. See the detailed information in Table 3 and Table S2 in Supplementary Materials .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples scored positive for Mycoplasma were examined with speci c primers for M. haemocanis (Mhc) and for Candidatus M. haematoparvum (CMhp) to detect coinfections [47,48]. Trypanosoma cruzi was detected and quanti ed by real-time PCR following the protocols described by Ye -Quintero et al [49]. Leishmania spp.…”
Section: Laboratory Analysismentioning
confidence: 99%